Penerapan Strategi Lindung Nilai Pada Perusahaan Otomotif: Studi Kasus PT Astra International TBK Sektor Otomotif (International Forum of Researchers and Lecturers, 2024)
The importance of hedging is manifested in an international context, multinational companies face unique challenges related to currency fluctuations and geopolitical risks. PT Astra as a leading company in Indonesia with a very diverse business portfolio, is an interesting subject to be researched related to the strategies and hedging practices applied. Hedging can be done through various financial instruments such as futures, options, swaps, and other derivative instruments. PT Astra has successfully implemented an effective hedging strategy in dealing with risks in the automotive industry. This success is supported by the involvement of related parties, coordination between departments, and a good understanding of risk factors.